PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GEOGEBRA TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA MI NW DARUL IKHWAN KARANG ANYAR TAHUN AJARAN 2024/2025 - Nisfun Laeli; Doni Septu Marsa Ibrahim; Iwan Usma Wardan; Muh. Yazid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using GeoGebra as a learning media on student learning outcomes in Mathematics at MIS NW Darul Ikhwan Kembang Sari, Academic Year 2024/2025. The research used an experimental design with a one-group pretest-posttest. Sampling was conducted using a saturated sampling technique. The subjects of this study were 15 students. The research instrument was a multiple-choice test. The prerequisite test used was the Liliefors test to verify data normality. The results of the normality test showed that the population was normally distributed. The results showed that the average pretest score was 49.047 and the average posttest score was 84.28. The results of the multiple-choice hypothesis test using the paired sample t-test yielded a calculated t-value of -5.362. If the calculated t-value is compared to the t-table (dk = n-1 = 15 - 1 = 14) with a 5% significance level, the result is 2.163. Therefore, it can be concluded that the calculated t-value is greater than the t-table (-5.362> 2.163). Therefore, the proposed hypothesis can be accepted, namely "H₀" is rejected, and "Hₐ" is accepted, which indicates that the use of GeoGebra learning media has an effect on student learning outcomes in mathematics at MIS NW Darul Ikhwan Kembang Sari in the 2024/2025 academic year